O que quer que se diga sobre Rui Mário Gonçalves não é tudo… - Filipa Coimbra; Joana Baião (Midas: Museus e Estudos Interdisciplinares)
The critic and art historian Rui Mário Gonçalves (1934-2014) is an essential personality within the Portuguese cultural milieu. His action lasted for several decades, from the 1960’s onwards, leaving his mark on Portuguese contemporary art historiography. Based on the analysis of the Calouste Gulbenkian Foundation (FCG)’s archives, some of the most important moments in the relationship between Rui Mário Gonçalves and the FCG are listed – from his formative period, which was marked by his stay in Paris (supported by this institution), to the affirmation and consolidation of his career as an historian and art critic. In this respect, special attention is given to his role in the exhibitions promoted by the FCG, either as a critic or as a direct participant. Rather than offering an in-depth review of Rui Mário Gonçalves’s cultural and artistic biography, this article aims to give a contribution to the study of his life and activity, pointing out several issues that could – and should – be the subject of future research.